x-(2-x)=-2x(-2x-4)

Simple and best practice solution for x-(2-x)=-2x(-2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(2-x)=-2x(-2x-4) equation:


Simplifying
x + -1(2 + -1x) = -2x(-2x + -4)
x + (2 * -1 + -1x * -1) = -2x(-2x + -4)
x + (-2 + 1x) = -2x(-2x + -4)

Reorder the terms:
-2 + x + 1x = -2x(-2x + -4)

Combine like terms: x + 1x = 2x
-2 + 2x = -2x(-2x + -4)

Reorder the terms:
-2 + 2x = -2x(-4 + -2x)
-2 + 2x = (-4 * -2x + -2x * -2x)
-2 + 2x = (8x + 4x2)

Solving
-2 + 2x = 8x + 4x2

Solving for variable 'x'.

Combine like terms: 2x + -8x = -6x
-2 + -6x + -4x2 = 8x + 4x2 + -8x + -4x2

Reorder the terms:
-2 + -6x + -4x2 = 8x + -8x + 4x2 + -4x2

Combine like terms: 8x + -8x = 0
-2 + -6x + -4x2 = 0 + 4x2 + -4x2
-2 + -6x + -4x2 = 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-2 + -6x + -4x2 = 0

Factor out the Greatest Common Factor (GCF), '-2'.
-2(1 + 3x + 2x2) = 0

Factor a trinomial.
-2((1 + x)(1 + 2x)) = 0

Ignore the factor -2.

Subproblem 1

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5

Solution

x = {-1, -0.5}

See similar equations:

| log125x=1/3 | | 2(2x)-12=2x-4 | | 9x-20+12+60=180 | | 6=7a+6a | | (3/(x-2))-(2/x)0 | | (3/(x-2))-(2/x) | | x-45=2.3 | | 6x-2(4x+5)=x-8 | | 4-3(1-2x)= | | x^3+4x^2-6=0 | | 7+2(3x+5)= | | 2(3x-9)-10=3x-13 | | 1.2x+10=1.4x+54 | | 3x-13=y-4 | | 11x^2+33x+12=0 | | F(x)=(x-3)(x-4i)(x-4i) | | 672=12(-7x-21) | | 63-7x=-3-189 | | 5x+5x+2+7=6x+4+3 | | 36+9264= | | -3(10+6)=-66 | | 7x=169 | | 2cos^2x+sinx+1=0 | | -3(10+6x)=-66 | | -4x+8=x+7 | | x^4-4x^3+30x^2-100x+125=0 | | -1+15x=180 | | -x+6y=11+x | | 5/9=m/63= | | x^3+0.2x^2-0.00000000000112=0 | | 2x+8y=-2-2x | | -4(x-5)=2(x+2)+1 |

Equations solver categories